Grads on the Go: Measuring College-Specific Labor Markets for Graduates - Johnathan G. Conzelmann; Steven W. Hemelt; Brad J. Hershbein; Shawn Martin; Andew Simon; Kevin Stange (Institute of Labor Economics (IZA), 2022)
This paper introduces a new measure of the labor markets served by colleges and universities across the United States. About 50 percent of recent college graduates are living and working in the metro area nearest the institution they attended, with this figure climbing to 67 percent in-state. The geographic dispersion of alumni is more than twice as great for highly selective 4-year institutions as for 2-year institutions. However, more than one-quarter of 2-year institutions disperse alumni more diversely than the average public 4-year institution. In one application of these data, we find that the average strength of the labor market to which a college sends its graduates predicts college-specific intergenerational economic mobility. In a second application, we quantify the extent of "brain drain" across areas and illustrate the importance of considering migration patterns of college graduates when estimating the social return on public investment in higher education.
Keywords: I23; I25; J21; J40; J61; 330; colleges; labor markets; postsecondary education; economic mobility